Stacked wire mesh monoliths for the simultaneous abatement of VOCs and diesel soot - Godoy, Maria Laura (2018)
Structured catalysts based on Pt,CeO2 deposited on stainless steel wire meshes were developed to build catalytic cartridges for the treatment of diesel exhaust gases. The cartridges were tested for the simultaneous combustion of volatile organic compounds (VOCs) and soot. To this end, n-hexane, acetyl acetate, and toluene were selected as probe molecules. Each of them were loaded together with real soot into the cartridges showing that while VOCs abatement takes place between 200 °C and 350 °C, soot combustion occurs in the 300-500 °C temperature range with an average maximum combustion rate at 420 °C. The catalytic cartridges were characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and Brunauer-Emmett-Teller (BET) techniques. The mechanical stability of the coatings was confirmed by the ultrasound method. Air permeability of the cartridges prepared with different mesh sizes was also measured and the results were correlated using the Payri equation.